2015
DOI: 10.15845/noril.v7i1.222
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technology Literacy Skills and Class Instruction: a Comprehensive Perception Survey of University of Benin First Year Students

Abstract: This study investigates the influence of class instruction (GST 111 – use of library) on University of Benin (UNIBEN) first year students’ information and communication technology (ICT) literacy skills. The study adopted the survey research method using the questionnaire as research instrument. First year students in the 2013/2014 academic session constituted the population of study. Simple random and total enumeration sampling methods were used to collect data from students in five out of twelve faculties in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…It is concluded that there is no meaningful difference between opinions of government student and private student towards ICT. The findings of this test are supporting to the results of Luke (2015). Alternatively, hypothesis H01A "There is significant difference between perception of government and private student towards information and communication technology", is failed to accept.…”
Section: Testing Of Hypothesessupporting
confidence: 67%
“…It is concluded that there is no meaningful difference between opinions of government student and private student towards ICT. The findings of this test are supporting to the results of Luke (2015). Alternatively, hypothesis H01A "There is significant difference between perception of government and private student towards information and communication technology", is failed to accept.…”
Section: Testing Of Hypothesessupporting
confidence: 67%
“…Table 1 shows the relevant information literacy competencies that an information literate individual must-have. The competencies were adopted from prior studies on information literacy (Kegal and Wieringa, 2016; Martin and Gruziecki, 2015; Obasuyi, 2015). When compared with the results gathered, it is evident that the students lack information literacy competencies.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 provides the data set for the study. The variables used for information literacy have been adopted from prior studies on information literacy and digital literacy (Kegal and Wieringa, 2016; Martin and Gruziecki, 2015; Obasuyi, 2015). The variables I1- I10 represent the information literacy variables.…”
Section: Data Setmentioning
confidence: 99%
“…The list of items were adopted and modified from the following sources (Simons et al. , 2017; Kegal and Wieringa, 2016; University at Buffalo, 2016; Martin and Grudziecki, 2015; Obasuyi, 2015; Gray, 2012; The Open University, 2012). The setting of the study was considered while the items were selected for the study.…”
Section: Methodsmentioning
confidence: 99%